A new species and a new record of the Simulium (Gomphostilbia) gombakense species-group (Diptera: Simuliidae) from Thailand - Takaoka, Hiroyuki; Srisuka, Wichai; Low, Van Lun; Saeung, Atiporn (Elsevier, 2018)
Larvae and adults reared from pupae of Simulium (Gomphostilbia) gombakense Takaoka & Davies from eight streams in five provinces of Thailand were genetically analyzed by using cytochrome c oxidase subunit 1 sequences. The material was composed of four lineages, of which lineages 2, 3 and 4 are genetically closely related to one another, but more distantly related to lineage 1, which is equivalent to typical S. (G.) gombakense from Peninsular Malaysia. Lineages 2, 3 and 4, which are morphologically indistinguishable, are designated as genoforms A, B and C within a species complex of S. (G.) paiense sp. nov., which is described based on specimens of lineage 2 (=genoform A). Simulium (G.) paiense sp. nov. is similar to S. (G.) gombakense from Peninsular Malaysia but appears to be barely distinguished by the relative length of the female fore basitarsus. Simulium (G.) thuathienense Takaoka & Sofian-Azirun is newly recorded from Thailand and its male is described for the first time. The female of S. (G.) gombakense is briefly described based on females reared from pupae collected from Peninsular Malaysia.